Application of smartphone as a digital image colorimetric detector for batch and flow-based acid-base titration - Janejira Chanla (2020)
© 2019, Chiang Mai University. All rights reserved. In this research, we have developed the batch and flow-based system of titrimetric analysis by using a mobile phone as a detector. The digital image colorimetric detection system was set up with economic devices and to be easy to use by taking photograph with mobile phone camera, then the RGB signals were read from the RGB color picker application to calculate the RGB-based value and plot titration curve for evaluating the equivalence point. This method was applied to analyze samples of acid-base on daily basis, compared with the potentiometric and photometric titrations that using pH meter and spectrophotometer as a detector, respectively. The method was highly reproducible with the relative standard deviation of 1.14 % (n=11) for 0.5 %w/v of acetic acid standard solution. The proposed method was applied to the determination of acetic acid in vinegar and titratable acidity in fruit juices. Concentrations of acetic acid were found to be in a range of 5.23-5.35 %w/v. Concentrations of titratable acidity in the juice samples were found to be in a range of 0.27-0.50 %w/v. Thereafter, an analytical application involving the determination of the total alkalinity in mineral waters was performed, and it was found in the range of 11.50-18.50 mg/L of CaCO3 which were in good agreement with the results obtained from the standard method at the 95 % confidence level.